2002
DOI: 10.1046/j.1365-294x.2002.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of low gene flow in a neotropical clustered tree species in two rainforest stands of French Guiana

Abstract: The spatial genetic structure of the neotropical, clustered tree species Vouacapoua americana (Aublet) was studied in two natural forest stands (Paracou and Nouragues) in French Guiana. Using eight microsatellite loci, V. americana is characterized by a marked genetic structure at small spatial distances (under 30-60 m), in agreement with the limited seed dispersal by rodent species. Gene flow through pollen is also shown to be mainly restricted to less than 100 m. This result suggests that most pollination ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 76 publications
7
55
1
2
Order By: Relevance
“…The Sp values observed in this study, reflecting significant levels of SGS for both populations, are among the highest observed in tree species (see Table 1; Vekemans and Hardy, 2004) and similar to those observed for Vouacapoua americana, which is a tropical hardwood, also characterized as an outcrosser (Dutech et al, 2002). Our findings may have been influenced by the exhaustive sampling strategy we adopted, as well as the ecology of the species.…”
Section: Discussionsupporting
confidence: 83%
“…The Sp values observed in this study, reflecting significant levels of SGS for both populations, are among the highest observed in tree species (see Table 1; Vekemans and Hardy, 2004) and similar to those observed for Vouacapoua americana, which is a tropical hardwood, also characterized as an outcrosser (Dutech et al, 2002). Our findings may have been influenced by the exhaustive sampling strategy we adopted, as well as the ecology of the species.…”
Section: Discussionsupporting
confidence: 83%
“…The availability of highly variable molecular markers has facilitated the analysis of fine-scale genetic structure in natural tree populations. The fine-scale structure has been found in some forest tree species (Sork et al, 1993;Berg and Hamrick, 1995;Streiff et al, 1998;Dutech et al, 2002;Hardy et al, 2006). These tree species are characterized by either limited seed dispersal or restricted pollen and seed dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…II), which varied from 0.026 to 0.168, should be considered as low to high. Dutech et al [12,13] found in Vacapoua americana values from 0.008 to 0.195, and a high genetic differentiation among patches, with a global Fst of 0.11.…”
Section: Population Structurementioning
confidence: 98%